ACTUALIZATION OF THE TEACHINGS OF THE QURAN AT HAJAR ASWAD ISLAMIC BOARDING SCHOOL NGAWEN GUNUNGKIDUL YOGYAKARTA - Ahmad Wahyu Sudrajad; Hanif Mudhofar; Ma’isyatusy Syarifah (Bajang Institute, 2025)
This study examines the actualization of Qur'anic teachings related to the values of Education for Sustainable Development (ESD) at Pondok Pesantren Hajar Aswad, Ngawen, Gunung Kidul, Yogyakarta. This research employs a descriptive qualitative approach using observation, in-depth interviews, and document analysis as methods. The pesantren integrates ESD concepts with Islamic values through environmentally friendly programs such as the Green House and Mini Zoo, which empower students in environmental stewardship and skill development. The findings indicate that Islamic teachings, particularly the Qur'an, support ESD principles in maintaining environmental sustainability, which have been practically implemented by the pesantren. This research contributes to understanding the relevance of religious values and sustainable education practices in Islamic boarding schools.